Numerical solution of an integral equation from point process theory - Anderssen, R.; Baddeley, Adrian; de Hoog, F.; Nair, G. (Rocky Mountain Mathematics Consortium, 2014)
We propose and analyze methods for the numerical solution of an integral equation which arises in statistical physics and spatial statistics. Instances of this equation include the Mean Field, Poisson-Boltzmann and Emden equations for the density of a molecular gas, and the Poisson saddlepoint approximation for the intensity of a spatial point process. Conditions are established under which the Picard iteration and the under relaxation iteration converge. Numerical validation is included.